Africa : Economic Partnership Agreements between Africa and the European Union, What to do Now? Summary Report - World Bank (Washington, DC, 2012)
This report addresses the question raised in its title - now that 18 interim Economic Partnership Agreements (EPAs) have been initialed and negotiations of full EPAs have been launched, what should African countries and regional EPA-groups do? Part two of the report analyzes the outcome of the EPA negotiations thus far, the interim EPAs' implications for the trade and related policies of participating African countries, and the reforms required for successful implementation of interim EPAs. Part three examines the potential role of full EPAs, in advancing regional trade integration, open trade policies, and the liberalization of trade in services and foreign direct investment in Africa. The intended audience for this report is primarily policy makers and their advisors in the African EPA-countries, but it may also be of interest to those in the broader development community concerned with Africa.